CURSING, SEXUAL HARASSMENT, PROFANITY, OBSCENITY AND EPITHET IN DALLAS BUYERS CLUB MOVIE - Imelda Woa Wene; Ouda Teda Ena (JOALL (Journal of Applied Linguistics and Literature), 2020)
Taboo words are words that are strictly prohibited to be used due to the fact that they may cause misunderstanding or conflict and are not appropriate. Therefore, it is important to understand taboo words in order to avoid using inappropriate words.This studyexamines the use of taboo words by the characters in Dallas Buyers Club movie. It focuses on the types of taboo words and reasons that influence the characters to use taboo words in the movie. This study used content analysis method as the research method. The sources of data were the movie and its transcription. The researchers obtained the data from the characters’ utterances. This study finds there are five types of taboo words, namely cursing, profanity, obscenity, epithet and sexual harassment. Cursing is the most frequently taboo word used by the characters in the movie. The researchers also find that he reasons for using the taboo words are humor, psychological condition, ethnic group identity and social class. Psychological condition is the dominant reason for the characters’ use of taboo words. The result of this study provides an in-depth understanding of the usage of English taboo words in movies that might influence young English learners.